(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background- In March 2020, the WHO declared the COVID-19 outbreak a pandemic. COVID-19 pandemic has affected many aspects of the people’s life including physical, social, emotional and behavioral wellbeing. Objective- Assessing Knowledge, Attitude and Practice (KAP) Towards COVID-19 Vaccination among the general population and to evaluate Factors associated with Vaccine acceptance in general population. Methods- This web-based cross-sectional survey targeted general population aged 18 years to 45 years. A pre-validated questionnaire was administered to subjects who volunteered to be part of a survey and the responses were filled. An online questionnaire was administered to a sample (n= 100) drawn from general population, to assess their knowledge, attitude, perceptions, social media exposure, social norms, trust and their intentions to take up the Covid-19 vaccine. Due to Covid 19 situation the entire study was based only on the Google form Questionnaire & it was collected from the general population. Results- The sample had a predominance of female participants (73%) and the rest (27%) male participants. Most participants belonged to the 18-29 years of age group (97%) and maximum of participants resided in urban area (74%) and the rest (26%) resided in rural area. Most participants belonged to the middle socio-economic class (85%). 84% of study participants had a good knowledge of the statement that people after recovering with COVID-19 can take vaccine. Various motivating factors influencing them to get vaccinated include perception that there is no harm in getting vaccinated (61%), more than half of participants believe that taking Covid-19 Vaccine is a Societal Responsibility (61%) and its benefits outweigh the risks involved (46%). Conclusion- Attitude towards the importance of vaccine that it protect the people from covid-19 and preventive measures like wearing mask & social distancing should be followed even after Getting COVID-19 vaccine and they also shows positive attitude that they will encourage their family and friends to get vaccinated.